Trading and Voting - Musto, David K.; Yılmaz, Bilge (Journal of Political Economy, 2003)
Complete financial markets transform the political choice between candidates with different redistribution policies. If redistribution policies do not affect aggregate wealth, then financial trade implies that wealth considerations have no effect on voting and so do not affect who wins. However, an election in which one candidate would redistribute results in redistribution, and redistribution is the same whether or not he wins. Furthermore, he proposes, and if elected carries out, more redistribution than he prefers. If redistribution policies do affect aggregate wealth, then everybody expects more wealth if the candidate with the higher aggregate‐wealth policy wins.